Pengaruh Tingkat Pendidikan, Pelatihan Dan Motivasi Terhadap Kinerja Aparatur Desa Di Kecamatan Oba Tengah Kota Tidore Kepulauan - Lestari, Ayu; Dahlan, Fadli; Yunus, Imran (Jurnal Ilmiah Wahana Pendidikan, 2025)
The purpose of this study is to determine the effect of education level, training, and motivation on the performance of village officials in Oba Tengah District, Tidore Kepulauan City. This study uses quantitative methods and data analysis using multiple linear regression. The sample in this study consisted of 109 respondents. The results of the simultaneous test showed that the F count was 9.917 > 2.69 with a significance level of 0.00 < 0.05. This means that education level, training, and motivation simultaneously and jointly have a significant effect on the performance of village officials. However, in terms of partial variables, the level of education with a T value of 3.048 > T table 1.659. With a significance level of 0.003 < 0.05, this means that the level of education has an effect on the performance of village officials. Meanwhile, the training variable with a T value of 0.580 < T table 1.659. With a significance level of 0.563 > 0.05. This means that training does not affect the performance of village officials. The motivation variable has a T-value of 1.197 < 1.659. With a significance level of 0.234 > 0.05, this means that motivation does not affect the performance of village officials.